RETRACTED: Ikzf2 Regulates the Development of ICOS+ Th Cells to Mediate Immune Response in the Spleen of S. japonicum-Infected C57BL/6 Mice - Xie, Shihao; Wei, Haixia; Peng, Anping; Xie, Anqi; Li, Jiajie; Fang, Chao; Shi, Feihu; Yang, Quan; Huang, He; Xie, Hongyan; Pan, Xingfei; Tian, Xu; et al. (Frontiers in Immunology, 2021)
Background: Th cells (helper T cells) have multiple functions in Schistosoma japonicum (S. japonicum) infection. ICOS is induced and expressed in activated T lymphocytes, which enhances the development of B cells and antibody production through ICOS/ICOSL pathway. It remains unclear about the role and possible regulating mechanism of ICOS+ Th cells in the spleen of S. japonicum infected C57BL/6 mice. Methods: C57BL/6 mice infected with cercariae of S. japonicum through the abdomen. The expression of ICOS, activation markers, and the cytokine production on CD4+ ICOS+ Th cells were detected by Flow Cytometry (FCM) and Quantitative Real-Time PCR (qRT-PCR). Moreover, the differentially expressed gene data of ICOS+ and ICOS- Th cells from the spleen of infected mice were obtained by mRNA sequencing. Besides, western blot and chromatin immunoprecipitation (ChIP) was used to explore the role of Ikzf2 on ICOS expression. Results: After S. japonicum infection, the expression of ICOS molecules gradually increased in splenic lymphocytes, especially in Th cells (P < 0.01). Compared with ICOS- Th cells, More ICOS+ Th cells expressing CD69, CD25, CXCR5, and CD40L (P < 0.05), while less of them expressing CD62L (P < 0.05). Also, ICOS+ Th cells expressed more cytokines, such as IFN-γ, IL-4, IL-10, IL-2, and IL-21 (P < 0.05). RNA sequencing results showed that many transcription factors were increased significantly in ICOS+ Th cells, especially Ikzf2 (P < 0.05). Next, the expression of Ikzf2 was verified to be significantly increased and mainly located in the nuclear of ICOS+ Th cells. Finally, ChIP experiments confirmed that Ikzf2 could directly bind to the ICOS promoter in Th cells. Conclusion: In this study, ICOS+ Th cells were found to play an important role in S. japonicum infection to induce immune response in the spleen of C57BL/6 mice. Additionally, Ikzf2 was found to be one important transcription factor that could regulate the expression of ICOS in the spleen of S. japonicum infected C57BL/6 mice.